2022
DOI: 10.3389/fnut.2022.868336
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Preoperative Nutritional Assessment and Neutrophil-to-Lymphocyte Ratio in Patients With Thymic Epithelial Tumors

Abstract: IntroductionSystemic nutrition and immune inflammation are the key factors in cancer development and metastasis. This study aimed to compare and assess four nutritional status and immune indicators: prognostic nutritional index (PNI), nutritional risk index (NRI), neutrophil-to-lymphocyte ratio (NLR), and the systemic immune-inflammatory index (SII) as prognostic indicators for patients with thymic epithelial tumors.MaterialsWe retrospectively reviewed 154 patients who underwent thymic epithelial tumor resecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Furthermore, multiple studies have found different optimal critical values of PNI for predicting cancer prognosis. 9 , 10 Thus, the goal of this study was to determine the predictive value of PNI in patients with resectable AGE in terms of relapse-free survival (RFS) and overall survival (OS).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, multiple studies have found different optimal critical values of PNI for predicting cancer prognosis. 9 , 10 Thus, the goal of this study was to determine the predictive value of PNI in patients with resectable AGE in terms of relapse-free survival (RFS) and overall survival (OS).…”
Section: Introductionmentioning
confidence: 99%
“…There are several novel studies found that albumin and the NLR play critical roles in the immune and systemic inflammation status of patients. Huang et al [34] reported that albumin and NLR were associated with the overall survival of patients with thymic epithelial tumors. Li et al [35] demonstrated that low levels of albumin and high levels of NLR were identified as risk factors for poor prognoses patients who underwent surgical treatment for endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al . [ 34 ] reported that albumin and NLR were associated with the overall survival of patients with thymic epithelial tumors. Li et al .…”
Section: Discussionmentioning
confidence: 99%